Sharia Compliance in the Online-Based Sharia Mutual Funds: Bibit Application - Sulasiah Al Mujarodah; Syahrul A'dam (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2024)
This study aims to analyze the practice of an online-based Sharia mutual fund, Bibit. Bibit application is a digital platform opening opportunities for Muslims to invest in the Sharia-based capital market. This is a doctrinal legal study, relying on various fatwas issued by the National Sharia Board of the Indonesian Ulama Council (DSN-MUI) regulating Sharia contracts and transactions to analyze Sharia compliance with the Bibit application. This study finds that there are still gaps in the Sharia compliance of Bibit application, where improvements can be made. Some of the gaps include the use of non-Islamic banks as custodian banks, the uninformed investors of their fund use, and the system that is still based on profit rather than the principle of partnership.